WHERE WE ARE GOING? (review of Vasily Tkachenko’s book "Ukraine. Where we go?") - Kononenko, P. (Bulletin of Taras Shevchenko National University of Kyiv. Philosophy, 2018)
Review of Vasily Tkachenko’s book "Ukraine. Where are we going?" (Kiev, Logos Ukraine publishing house, 2017).